Engineering The Megacity. - Hassler, S.
This report focuses on how to solve some of the big engineering challenges we face as the world's cities multiply, grow, and mature, particularly as they are being played out in the largest and most complicated urban habitats human beings have ever lived in: megacities. Not all of the challenges of urban life have a technological solution, of course. But we found five cities Shanghai, Sao Paulo, Mumbai, Tokyo, and New York - that have come up with particularly innovative solutions to some of the biggest problems cities face: pollution, transportation, energy, natural disaster, and crime.
Keywords: Mumbai; New York; Sao Paulo; Shanghai; Tokyo; Crime; Ecocity; Energy; Megacity; Natural disaster; Pollution; Transportation; Urban development; Urban technology